Romance Negro de Rubem Fonseca: conto fantástico ou narrativa policial? - Camarani, Ana Luiza [UNESP]; Telarolli, Sylvia [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
Este artigo analisa o conto Romance Negro, de Rubem Fonseca, a partir do duplo sentido que o autor dá à expressão roman noir, a qual remete, em literatura, seja ao gênero que se desenvolveu no pré-romantismo inglês da segunda metade do século XVIII, seja a um tipo de romance policial americano do século XX chamado de noir. Aproveitando essa dualidade do termo, o autor cria uma narrativa híbrida ao mesclar dois gêneros: o romance gótico e a narrativa policial.

The expression noir fiction can refer to the genre that flourished in the eighteenth century pre-romantic English literature or to the twentieth century American police novel called noir. This essay analyses Rubem Fonseca’s short story entitled “Romance negro” based on the double meaning that the author gives to the expression noir novel. Taking advantage of the duality of the term, the author creates a hybrid narrative that brings together two different genres: gothic novel and police narrative.
Rubem Fonseca’s “Romance Negro”: fantastic tale or police narrative?
Keywords: Literatura brasileira; Literatura contemporânea; Conto fantástico; Intertextualidade; Brazilian literature; Contemporary literature; Fantastic tale; Intertextuality